2018
DOI: 10.3390/nu10091137
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Astaxanthin on Oxidative Stress-Induced Mitochondrial Dysfunction-A Mini-Review

Abstract: Oxidative stress is a major contributor to the pathogenesis of various human diseases as well as to the aging process. Mitochondria, as the center of cellular metabolism and major regulators of redox balance, play a critical role in disease development and progression. Mitochondrial dysfunction involving structural and metabolic impairment is prominent in oxidative stress-related diseases. Increased oxidative stress can damage mitochondria, and subsequent mitochondrial dysfunction generates excesses of mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 75 publications
2
124
0
1
Order By: Relevance
“…The effects of natural AX in humans have been reviewed in more than 20 publications over the last 10 years and include studies on antioxidation, hepatoprotection, eye function, skin health, immune response, inflammation, gastric ulcer, cardiovascular system, muscle endurance, cancer, central nervous system, male fertility, metabolic syndrome, diabetes, and mitochondrial dysfunction (Ekpe, Inaku, & Ekpe, ; Fakhri, Abbaszadeh, Dargahi, & Jorjani, ; Fassett et al, , Fassett & Coombes, ; Galasso et al, ; Visioli & Artaria, ; Brown, Gough, Deb, Sparks, & McNaughton, ; Capelli, Jenkins, & Cysewski, ; Davinelli, Nielsen, & Scapagnini, ; Kim & Kim, ; Yamashita, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of natural AX in humans have been reviewed in more than 20 publications over the last 10 years and include studies on antioxidation, hepatoprotection, eye function, skin health, immune response, inflammation, gastric ulcer, cardiovascular system, muscle endurance, cancer, central nervous system, male fertility, metabolic syndrome, diabetes, and mitochondrial dysfunction (Ekpe, Inaku, & Ekpe, ; Fakhri, Abbaszadeh, Dargahi, & Jorjani, ; Fassett et al, , Fassett & Coombes, ; Galasso et al, ; Visioli & Artaria, ; Brown, Gough, Deb, Sparks, & McNaughton, ; Capelli, Jenkins, & Cysewski, ; Davinelli, Nielsen, & Scapagnini, ; Kim & Kim, ; Yamashita, ).…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviations: ACNFP, Advisory Committee on Novel Foods and Processes; FSAI, Food Safety Authority of Ireland; NFA, National Food Administration. Fassett et al, 2008, Fassett & Coombes, 2012Galasso et al, 2018;Visioli & Artaria, 2017;Brown, Gough, Deb, Sparks, & McNaughton, 2018;Capelli, Jenkins, & Cysewski, 2013;Davinelli, Nielsen, & Scapagnini, 2018;Kim & Kim, 2018;.…”
Section: Clinical Safety Of Natural Axmentioning
confidence: 99%
“…Astaxanthin (3,30-dihydroxy-ÎČ, ÎČ-carotene-4,40-dione) is a red pigment belonging to the sub-class of xanthophyllic carotenoids; it is found mainly in microalgae, mushrooms, and complex plants, as well as in salmon, trout, and crustacean cells [114]. Astaxanthin shows strong antioxidative properties and can neutralize singlet oxygen and free radicals, thus, preventing lipid peroxidation [173]. Its properties are due to the presence of numerous conjugated multiple bonds.…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“…Its properties are due to the presence of numerous conjugated multiple bonds. It has been demonstrated that the most important effects of astaxanthin's activity include the prevention of neuron damage and inhibition of cell membrane peroxidation [173]. Astaxanthin is composed of a long, nonpolar, conjugated bond connecting polar ion rings located on both ends of the chain.…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“…ATX, with its superior anti-oxidant and anti-inflammatory properties, exhibits protective effects in cardiovascular health and disease, ischemia and reperfusion injury, cognitive function with age, and neurodegeneration [16]. However, its use in the food, feed, and pharmaceutical fields is limited, owing to low bioavailability, poor stability during thermochemical treatments, susceptibility to oxidation, and poor organoleptic characteristics.…”
Section: Discussionmentioning
confidence: 99%